Strategi Manajemen Sumber Daya Manusia dalam Pengelolaan Keuangan BUMDES di Era Digitalisasi - Renya Rosari; Pandu Adi Cakranegara; Ratih Pratiwi; Irsyad Kamal; Chitra Indah Sari (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study is to analyze human resource management strategies in digitally managing BUMDes finances. The demand for the use of digitization must indeed be implemented to make it easier in the world of work. Digitalized financial reports can make it easier for BUMDes business owners to obtain information and data that is systematically arranged. This research method uses a qualitative method with a literature review approach. The data sources are taken from references to the Village Government Law, relevant research journals and books on village financial management. Data analysis using document analysis. The findings of this study are; BUMdes managers must be able to manage archives based on internationalization; BUMDes managers must be integrated in preparing financial SOPs; The BUMDes manager compiles correct digitizing accounting reports and administrative records so that they can provide management accountability in the use of capital participation funds that have been rolled out by the government.